2005
DOI: 10.1111/j.1365-3024.2005.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Host humoral immune response to Leishmania lipid‐binding protein

Abstract: SUMMARY We report on the use of Leishmania donovani lipid-binding proteins (LBPs) as antigens capable of being recognized by serum from immunocompetent patients from southern Spain suffering from visceral leishmaniasis and from Peruvian patients with localized cutaneous leishmaniasis caused by Leishmania braziliensis. The absorbance found by immunoenzymatic techniques gave significantly different results for the serum samples from patients with and without leishmaniasis. Specificity by ELISA testing was 93.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
2
5
0
1
Order By: Relevance
“…The aggregation process could be an intracellular tool to regulate the activity of these proteins in vivo, since the protein aggregates do not bind fatty acids (Fournier and Rahim, 1983). Analysis by mass spectrometry showed that the protein band with affinity toward fatty acids had a molecular weight of 8,215.96 kDa, identical to that obtained previously by Hasan, Diaz de la Guardia et al (2002) for proteins of G. lamblia and by Maache et al (2005) for Leishmania donovani.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The aggregation process could be an intracellular tool to regulate the activity of these proteins in vivo, since the protein aggregates do not bind fatty acids (Fournier and Rahim, 1983). Analysis by mass spectrometry showed that the protein band with affinity toward fatty acids had a molecular weight of 8,215.96 kDa, identical to that obtained previously by Hasan, Diaz de la Guardia et al (2002) for proteins of G. lamblia and by Maache et al (2005) for Leishmania donovani.…”
Section: Discussionsupporting
confidence: 84%
“…In helminths, for example, these molecules include HLBPs and FABPs. Recently, using an affinity column prepared with sepharose epoxy 4B and stearic acid as a ligand, our group has characterized proteins with a similar function in parasitic protozoans; these proteins exhibit a molecular weight of about 8 kDa (Hasan, Dias de la Guardia et al, 2002;Maache et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of immigrants in the study area was similar to that of other urban areas in Spain [31]. Several factors could have been responsible for the high percentage of VL in immigrants: migration of non-immune people from areas where L. infantum is not endemic [1,32], differences in host immune responses [33], and differences in living habits and/or health-seeking behaviour. These factors should be explored in further investigations.…”
Section: Figuresupporting
confidence: 60%
“…Nonprotein antigens such as lipid-binding proteins and 9-Oacetylated sialic acid have been shown to elicit humoral immune response (Maache et al 2005;Bandyopadhyay et al 2004). However, a major disadvantage of serological diagnosis is the persistence of antibodies for long periods after cure, and therefore one fails to distinguish past infection/asymptomatic cases.…”
Section: Parasitological Methods: High Specificity But Low Sensitivitymentioning
confidence: 99%